Penguatan Pengelolaan Wisata Lava Tour Merapi untuk Mendorong Kesejahteraan Masyarakat - I G A N Alit Sumantri; I Gusti Agung Ayu Pramita Indraswari; Budiadnyani, Ni Putu Budiadnyani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Merapi Lava Tour is a form of tourism based on the natural potential and history of disasters that has developed on the slopes of Mount Merapi. This tourism not only serves as a tourist attraction but also serves as a source of livelihood for the surrounding community. However, suboptimal management has resulted in less than optimal economic benefits for the community. This Community Service (PKM) activity aims to strengthen the management of the Merapi Lava Tour in order to encourage improved local community welfare. The methods used include a participatory approach through field observations, focus group discussions, and tourism management mentoring. The results of the activity indicate an increase in community understanding of sustainable tourism management, strengthening human resource capacity, and raising awareness of the importance of tourism services and collaboration between stakeholders. This activity is expected to contribute to creating professional tourism management that will have a direct impact on community welfare.